Advancing a qualitative turn in news media trust research. Issue 4 (30th January 2023) - Garusi, Diego; Splendore, Sergio
Abstract: The contemporary media environment represents the greatest challenge ever to journalism's legitimacy. Surveys conducted in different parts of the world highlight a decline in trust in news media. Due to the numerous changes in the news media environment, different investigative tools are required to grasp the mechanisms underlying news media trust from those adopted so far. This article provides a review of existing media trust research and argues that it is necessary to investigate news media trust (also) from a qualitative perspective because today understanding media trust is as crucial as measuring it.